Processed Foods and Gut Health: A Mini Review of Microbiome Responses - Baspakova, Akmaral; R. Zhilisbayeva, Kulyash; A. Umbetova, Aigerim; Zh. Abitova, Anara (West Kazakhstan Medical Journal, 2023)
The present mini review delves into the intricate nexus between processed foods and gut health, with a focused exploration of the dynamic responses exhibited by the gut microbiome. The ubiquity of processed foods in contemporary diets has prompted inquiries into their potential ramifications for human physiological well-being. Given the acknowledged centrality of the gut microbiota in sustaining holistic health, deciphering the nuances of how processed foods impinge upon its constitution and functionality assumes critical significance. By methodically scrutinizing recent empirical investigations, this mini review elucidates the multifaceted manners through which processed foods interface with the complex web of the gut microbial consortium. It meticulously delineates alterations in microbial taxonomic diversity, community richness, and ecological equilibrium, thereby elucidating the putative mechanistic underpinnings driving the possible impact of processed food consumption on physiological equilibrium. Furthermore, the review cogitates upon the broader translational repercussions of these microbiome perturbations, cogently contemplating potential correlations with pathophysiologies encompassing but not limited to inflammation cascades, metabolic perturbations, and immune homeostasis dysregulation. By synthesizing the current compendium of empirical insights, this mini review proffers cogent perspectives into the intricate interplay between processed foods and gut health. It substantiates the exigency for augmented investigative endeavors, whilst advocating for judicious dietary selections that foster resilience and equilibrium within the intricate milieu of the gut microbiome.